Comparative study of online learning and hybrid learning based on students’ habits of mind after COVID-19 pandemic - Aditya Prihandhika; Didi Suryadi; Sufyani Prabawanto (Mahesa Research Center, 2022)
The purpose of this study was to evaluate mathematics learning through online learning and hybrid learning which were reviewed based on the Habits of Mind (HoM) owned by 70 samples as the prospective mathematics teachers from a university in West Java, Indonesia. The research data was obtained from a questionnaire containing 26 statements referring to the HoM indicators. It was measured using a Likert scale and then analysed using the Mann Whitney-U test to see if there were differences in the achievement of HoM from the two sample groups that received the online learning and the hybrid learning method. The results showed that there was no difference in the achievement of HoM in the two groups with the average score still below the ideal score of each measured indicator. Based on these findings, the implementation of online learning and hybrid learning methods pay more attention to affective abilities so that the achievement of prospective mathematics teachers’ HoM in mathematics learning after the COVID-19 pandemic can be maximized.